"Reverse Centrifugal Movement": Reading Liminality at the Shrinescape - Syamsul Asri; Heddy Shri Ahimsa Putra; Albertus Bagus Laksana (Religio: Jurnal Studi Agama-agama, 2021)
This paper main objective is to explain the nature and dynamics of solidarity and kindness that being shown in arbain walk, an annual Shi`i pilgrimage where noticeable presence of non-Muslims are observed. Coming from different religious and ethnic backgrounds, these lovers of Imam Husain are united by Imam Husain`s barakah in one hand and epic hospitality of Iraqi people for Imam Husain`s millions of devotee in other hand. The paper argues that this is an elaborated form of liminality, as emerge and envelope the pilgrims in their shrine-related religious activity, cordially affected by its shrine centered pilgrimage, namely Imam Husain`s shrine, in which shrine`s materiality and its multilayered intellectual and spiritual narrativity determines the form and intensity of pilgrim`s comradeship that being sensed. Reverse centrifugal movement is a dynamics through which Imam Husain`s shrinescape shapes the form and intensity of mutual friendship that emerge during this bigger than hajj annual rite.